Bioremediation of diuron contaminated soils by a novel degrading microbial consortium. (1st March 2017) - Villaverde, J.; Rubio-Bellido, M.; Merchán, F.; Morillo, E.
Abstract: Diuron is a biologically active pollutant present in soil, water and sediments. It is persistent in soil, water and groundwater and slightly toxic to mammals and birds as well as moderately toxic to aquatic invertebrates. Its principal product of biodegradation, 3, 4-dichloroaniline, exhibits a higher toxicity than diuron and is also persistent in the environment. On this basis, the objective of the study was to determine the potential capacity of a proposed novel diuron-degrading microbial consortium (DMC) for achieving not only diuron degradation, but its mineralisation both in solution as well as in soils with different properties. The consortium was tested in a soil solution where diuron was the only carbon source, and more than 98.8% of the diuron initially added was mineralised after only a few days. The consortium was composed of three diuron-degrading strains, Arthrobacter sulfonivorans, Variovorax soli and Advenella sp. JRO, the latter had been isolated in our laboratory from a highly contaminated industrial site. This work shows for the first time the potential capacity of a member of the genus Advenella to remediate pesticide-contaminated soils. However, neither of the three strains separately achieved mineralisation (ring- 14 C) of diuron in a mineral medium (MSM) with a trace nutrient solution (NS); combined in pairs, they mineralised 40% of diuron in solution, but the most relevant result was obtained in the presence of the three-member consortium, where complete diuron mineralisation was achieved after only a few days. In the presence of the investigated soils in suspension, the capacity of the consortium to mineralise diuron was evaluated, achieving mineralisation of a wide range of herbicides from 22.9 to 69.0%. Highlights: The novel diuron-degrading microbial consortium was capable to mineralise diuron. The novel degrading isolate showed capacity for diuron biodegradation. The novel consortium mineralised diuron in solution and soil.